2012
DOI: 10.5152/balkanmedj.2012.034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antinociceptive and Neurotoxic Effects of Intrathecal Dexmedetomidine in Rats

Abstract: Objective: Dexmedetomidine has been reported to produce analgesia after intrathecal administration. In the present study the α2-adrenoceptor agonist dexmedetomidine was evaluated for its potential spinal neurotoxic effects.Material and Methods: Three days after intrathecal cannulation, rats were administered either dexmedetomidine (3 μg/30 μL, i.t.) or saline (30 μL, i.t.). Antinociceptive, sedative and motor effects of intrathecal administrations of dexmedetomidine or saline were evaluated during 90 min. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…'s study, intrathecal injections of dexmedetomidine at the dose of 10 μgr-1 produce antinociception but did not cause any histopathological sign of injury in the spinal cord. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…'s study, intrathecal injections of dexmedetomidine at the dose of 10 μgr-1 produce antinociception but did not cause any histopathological sign of injury in the spinal cord. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…Konakci et al . [ 25 28 ] reported moderate or severe demyelinization of myelin sheaths in the white matter when 10 μg dexmedetomidine was administered through the epidural route. This dose was the same dose used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have been conducted with intrathecal dexmedetomidine in dose range of 2.5–100 µg, however, risk of neurotoxicity cannot be denied at dosage more than three µg. [ 12 13 14 ] Human studies have shown that 3–15 µg of dexmedetomidine co-administered with local anaesthetics has a dose-dependent effect on anaesthesia, analgesia and haemodyanamic stability. [ 5 15 16 17 18 ] Similar results were seen with other α 2 AR agonist, clonidine, in doses of 15–45 µg when added to intrathecal local anaesthetic.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine is a potent and highly selective alpha 2-adrenoceptor agonist. Although dexmedetomidine has a number of undesirable side effects (diuresis, mydriasis, and sedation), intrathecal administration of dexmedetomidine has antinociceptive effects in animals [ 5 ]. Hence, a combination of several agents that produce synergistic interactions or similar therapeutic effects may also attenuate the undesired effects by permitting a diminution dose of individual agents to be administered.…”
Section: Letters To Editorsmentioning
confidence: 99%